Student Decision to Enter College in Bengkulu - Ririn Harini; Susiyanto Susiyanto; Onsardi Onsardi; Fitri Nur Hafidzah (UNIVED Press, 2024)
Universities in Indonesia face increasingly fierce competition in attracting prospective students to remain and compete with other universities, Muhammadiyah University of Bengkulu needs to apply factors that can influence student decisions. This research aims to examine the influence of social media marketing, university reputation, tuition fees, location, and product variations on students' decisions to study at UM Bengkulu. The data used is primary data. This research is included in quantitative research with a purposive sampling technique. The population of this research was all UM Bengkulu students, totaling 800 respondents. This research uses SEM-PLS version 4.0. The results of this research state that tuition fees, location, and product variety have a significant influence on student decisions, while social media marketing and university reputation have no influence on students' decisions to study at UM Bengkulu.